Поняття "лідерський потенціал" і "лідерські якості": зміст та використання у науковій думці - Романовський, Олександр Георгійович; Михайличенко, Валентина Євдокимівна; Гура, Тетяна Віталіївна (Національний технічний університет "Харківський політехнічний інститут", 2019)
Досліджено співвідношення лідерського потенціалу та лідерських якостей у студентів. Уточнено визначення поняття «лідерський потенціал» і «лідерські якості», розкритий їхній зміст. Вказано, що в цілому ряді робіт дослідників часто відбувається змішування цих понять, а іноді, і підміна один одним. Обґрунтовано необхідність не тільки діагностики лідерського потенціалу студентів, а й мобілізації його ресурсних можливостей, тобто вивчення шляхів і засобів його активізації та розвитку під час навчання у зво. Сформульовано висновок про необхідність дотримання єдиної концепції про зміст таких понять як «лідерські якості» і «лідерський потенціал», а також їхні повної термінологічної уніфікації.

The article is dedicated to the topical problem of studying leadership potential and leadership traits in students. The authors offer a definition of the notions of “leadership potential” and “leadership traits” and disclose their meanings. It is shown that in works by a number of researchers there often occurs a confusing mixing up of these notions, and sometimes their substitution. A point of view is expressed that leadership potential is possible to be developed, and leadership can be trained. There is substantiated the need in not only diagnostics of students’ leadership potential, but also in mobilizing its resource possibilities, that is search for ways and means to activate it during one’s training at a university. A conclusion is made on the need of working out a unified idea on the content of such notions as “leadership traits” and “leadership potential”, as well as their complete terminological unification.
The notions of leadership potential and leadership traits: content and usage in science mind
Keywords: процес навчання; діагностика; виявлення; teaching process; diagnostics; detection